Microextrusion Printing of Multilayer Hierarchically Organized Planar Nanostructures Based on NiO, (CeO2)0.8(Sm2O3)0.2 and La0.6Sr0.4Co0.2Fe0.8O3−δ - Tatiana L. Simonenko; Nikolay P. Simonenko; Philipp Yu. Gorobtsov; Elizaveta P. Simonenko; Nikolay T. Kuznetsov (Micromachines, 2022)
In this paper, NiO, La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) and (CeO2)0.8(Sm2O3)0.2 (SDC) nanopowders with different microstructures were obtained using hydrothermal and glycol–citrate methods. The microstructural features of the powders were examined using scanning electron microscopy (SEM). The obtained oxide powders were used to form functional inks for the sequential microextrusion printing of NiO-SDC, SDC and LSCF-SDC coatings with resulting three-layer structures of (NiO-SDC)/SDC/(LSCF-SDC) composition. The crystal structures of these layers were studied using an X-ray diffraction analysis, and the microstructures were studied using atomic force microscopy. Scanning capacitance microscopy was employed to build maps of capacitance gradient distribution over the surface of the oxide layers, and Kelvin probe force microscopy was utilized to map surface potential distribution and to estimate the work function values of the studied oxide layers. Using SEM and an energy-dispersive X-ray microanalysis, the cross-sectional area of the formed three-layer structure was analyzed—the interfacial boundary and the chemical element distribution over the surface of the cross-section were investigated. Using impedance spectroscopy, the temperature dependence of the electrical conductivity was also determined for the printed three-layer nanostructure.